Assessment of Stress Distribution Around Traditional and Sleeve Fixed Partial Denture Designs: Finite Element Analysis - Dimashkieh, Mohiddin R.; Yousief, Salah A.; Demachkia, Amir M. [UNESP]; Nassani, Mohammad Zakaria; Samran, Abdulaziz; Barakat, Ali; Singh, Yash Pal; Dimashkieh, Reda M.; El Sayed, Hend Mohamed; Galal, Rami M.; Noushad, Mohammed; Saini, Monika (Thieme, 2024)
Objectives: The aim of this research is to evaluate/compare the use of traditional versus sleeve fixed partial denture (PD) designs made from different materials on supporting structures. The comparison included three- and four-unit PD cases. Materials and Methods: Four finite element models are used in the research. The three-unit PD consists of the mandibular second premolar, first molar (as a pontic), and second molar. The four-unit PD includes the first premolar. The PD materials assessed were zirconia, E-max, and Celtra Duo. Bone has been simplified representing it as two cuboids. Each PD has been loaded to two cases over the pontic's central fossa: 300 N compressive, 150 N obliquely applied with 45 degrees forming 24 cases. Results: The three-unit traditional and sleeve PDs material change showed a slight change in cortical bone stress under vertical loading. Under oblique loading, cortical bone Von Mises stresses were higher by about 12 to 15% more than vertical loading. On the other hand, the four-unit PDs showed minor effect by changing PD material, while using sleeve design PD can reduce the cortical bone stresses up to 20% in comparison to traditional PD design. The mucosa and spongy bone were negligibly affected by changing PD material, and the traditional and sleeve designs showed close values to each other. Superiority of sleeve design appeared by reducing cement layer stresses dramatically, while PD body material rigidity affects its response. Conclusion: Within the limitations of this study, the higher rigid PD material can dissipate loadings over it more preferably regarding its effect on the underlying structures. Sleeve PD design is equivalent to the traditional one for three-unit PDs, while it showed better performance with four-unit PDs. Zirconia three-unit PDs' bodies received the lowest stresses and redistributed and transferred the applied load to the underneath structures better than the other two tested materials. This finding was reversed with four-unit PDs.
Keywords: Celta Duo; E-max; finite element analysis; partial denture; zirconia